SrO assisted 1393 glass scaffold with enhanced biological compatibility - Ali A.; Singh S.P.; Pyare R. (My University, 2025)
Being therapeutic ion strontium is often substituted for calcium to confer enhanced therapeutic potential in bioactive glasses. The present study deals with the evaluation of desired physico-chemical and biological compatibilities of SrO derived bioactive 1393 glass scaffolds. Herein, the SrO substituted for CaO (0, 5, 20, 50 and 100%) in 1393 glass based scaffolds (namely S1, S2, S3, S4 and S5) were prepared through the most versatile sol gel route followed by foam replica technique. The In-vitro bioactivity of the scaffolds characterized by XRD, FTIR, SEM-EDX, and pH behavior was enhanced by increasing SrO percentage in parent 1393 glass system. Physicomechanical properties were also considerably improved in SrO derived scaffolds than that of the pure glass system in both ‘as prepared’ and ‘during soaking in SBF’. Further, the formation of strontium hydroxycarbonated apatite [Sr-HCA; Ca(10-x)Srx(PO4)6-y(CO3)y(OH)2] layer on the SrO derived scaffolds have improved the cell-scaffold interactions and augmented the biocompatibility in SrO substituted scaffolds. Therefore, SrO derived 1393 glass scaffolds seem potential biomaterials for neo bone tissue regenerative application especially trabecular bones. © 2020 Elsevier B.V.